2022
DOI: 10.1038/s41419-022-04580-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological inhibition of XBP1 protects against APAP hepatotoxicity through the activation of autophagy

Abstract: Acetaminophen (APAP) hepatotoxicity induces endoplasmic reticulum (ER) stress which triggers the unfolded protein response (UPR) in hepatocytes. However, the mechanisms underlying ER stress remain poorly understood, thus reducing the options for exploring new pharmacological therapies for patients with hyperacute liver injury. Eight-to-twelve-week-old C57BL/6J Xbp1-floxed (Xbp1f/f) and hepatocyte-specific knockout Xbp1 mice (Xbp1∆hepa) were challenged with either high dose APAP [500 mg/kg] and sacrificed at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…To investigate the roles of autophagy in the regulation of PKM2 in inflamed-lung tissue, rapamycin, a widely used mTOR inhibitor and autophagy inducer ( Ye et al, 2022 ), was administered. As expected, administration of rapamycin increased the level of LC3B-II but decreased the level of p62 in LPS-insulted mice ( Figures 1G, H ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the roles of autophagy in the regulation of PKM2 in inflamed-lung tissue, rapamycin, a widely used mTOR inhibitor and autophagy inducer ( Ye et al, 2022 ), was administered. As expected, administration of rapamycin increased the level of LC3B-II but decreased the level of p62 in LPS-insulted mice ( Figures 1G, H ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that APAP triggers autophagy via the activation of epidermal growth factor receptor, transcription factor EB, PINK1/Parkin, and classical phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway. As a self-digestion process mediated by lysosomes, autophagy inhibits tissue damage by removing misfolded proteins, damaged organelles, and reactive oxygen species [ 40 ]. It includes initiation, nucleation, fusion, and hydrolysis between autophagosome and lysosome and is mainly performed by autophagy-related proteins (Atg).…”
Section: Discussionmentioning
confidence: 99%
“…[ 107 , 108 ] 4‐HNE induces endoplasmic reticulum (ER) stress to lead to hyperactivation of inositol‐requiring kinase 1 α (IRE1 α )‐X‐box binding protein 1 (XBP1). [ 109 , 110 ] XBP1 promotes aberrant lipid accumulation to manipulate metabolic signaling for DCs deactivation by enhancing fatty acid oxidation, which is closely related to the immature resting phenotype of DCs with the little secretion of cytokines and weak ability to activate T cells. [ 111 ] Collectively, lipid accumulation and ER stress inhibit TIDC activation in OC.…”
Section: Nanomedicines Improve Oc Antigen Presentationmentioning
confidence: 99%